Pengaruh Budaya Organiasi terhadap Kinerja Karyawan - Lubis, Dewi Shinta Wulandari (BISMA Cendekia, 2020)
This study aims to determine the effect of organizational culture on employee performance. This research was conducted on 66 employees of PT. Bandar Abadi Shipyard Batam who was the respondent. The variables observed in this study consisted of organizational culture and employee performance. Data were collected by distributing questionnaires and literature study, questionnaires were developed from the indicators of each variable which were the observations. The data test was conducted with validity and reliability, while the data analysis used simple linear regression, with hypothesis testing using the coefficient of determination and partial test. The results of this study indicate that organizational culture has a positive and significant effect on employee performance at PT. Bandar Abadi Shipyard.